EPIDEMIOLOGICAL CHARACTERISTICS OF PATIENTS WHO ARE NASAL CARRIER OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - Silva-Lamus Helen Carolina; Milanés-Pérez Rosa Isabel; Álvarez-Coneo Álvaro; Arzuza-Navarro Octavio (Revista Ciencias Biomédicas, 2015)
Introduction: to be nasal carrier of S. Aureus is considered a risk for nosocomial and community infections. The increasing behavior of the infections caused by strains of Methicillin-Resistant Staphylococcus Aureus (MRSA) in individuals with low or not one exposition to known risk factors indicate a variability in the microbiological and epidemiological behavior of these strains. Objectives: to describe sociodemographic and clinical characteristics of the adult outpatients, who attend to the otolaryngology consultation and present nasal disease and are nasal carriers of S. Aureus/MRSA. To establish the susceptibility patterns to antibiotics of the strains of isolated S aureus. Methods: Observational, descriptive and prospective study carried out in 226 patients who consulted for nasal alterations to the medical consultation of otolaryngology in the Hospital Universitario del Caribe, Cartagena, Colombia, since August 2012 to August 2013. A survey was done, just like samples by means of nasal swabs were taken and review of the clinical record and incubation and bacterial identification of nasal samples were carried out. Results: 226 patients were weighed up, 19 patients (8.4%) presented S. aureus and of these, 63.2% were methicillin-susceptible Staphylococcus aureus (MSSA) and 36.8% were documented as MRSA. The median of age in the patients with S. aureus was 41 years (IR= 26 – 54). The proportion of patients belonging to the female gender was 68.4%. Of the isolations with MRSA only the 28.6% came from Cartagena. The allergic rhinitis followed of turbinates hypertrophy were the most frequent Otolaryngologic conditions in these patients. No comparison was significant between the MRSS and MRSA. The antibiotic susceptibility patterns informed that strains of S. aureus were sensible to Linezolid, Gentamicin, Rifampicin, Vancomycin and Chloramphenicol. 94,7% were sensible to Levofloxacin and Tetracycline, 89.4% were sensible to Ciprofloxacin and 73.6% to Clindamycin. The intermediate susceptibility was demonstrated in the 52.6% for Erythromycin, 21% for Cefalotin, 10.5% for Clindamycin and 5.2% for Ciprofloxacin and Tetracycline. Finally, the antibiotic resistance had its higher percentage in the Penicillin with 84.2%, followed by 78.9% for Ampicillin, 52.6% Cefalotin, 36.8% for Oxacillin and 5.2% for Levofloxacin, Erythromycin and Ciprofloxacin. The Cefoxitin disk was used for the prediction of resistance to methicillin mediated by the mecA gene with positive results in 36.8% (7 patients). Conclusions: 7 (3.1%) of the 226 adult patients that were weighed up presented nasal isolation by SARM. This is the first report of colonization by MRSA isolations in outpatients of the otolaryngology consultation in a third level hospital in Cartagena, Colombia. Rev.cienc.biomed. 2015;6(1):85-95 KEYWORDS Staphylococcus aureus; Nasal mucosa; Bacterial Infections.